Performance of first Bi-2212 cable with pre-over pressure and over pressure heat treatment. (29th November 2021) - Yang, Dongsheng; Yu, Min; Ma, Hongjun; Zhang, Zhengchuang; Wang, Min; Liu, Sheng; Jin, Huan; Gao, Peng; Zhou, Chao; Liu, Fang; Liu, Huajun; Hao, Qingbin; et al.
Abstract: Due to the excellent current carrying performance of Bi2 Sr2 CaCu2 O8+ x (Bi-2212) and the development of its industrial manufacturing technology, Bi-2212 is a promising material to be developed as superconductor for application in fusion reactor magnets. The cable-in-conduit conductor (CICC) concept is often chosen for the development of large-scale magnets because of their high stability. Bi-2212 is presently the only kind of copper oxide superconducting material which can be made into solid round wire, which provides a good basis for developing CICCs. The over pressure (OP) heat treatment can significantly improve the superconducting performance of Bi-2212 wires but it also reduces the wire diameter by ∼5%. This leads to an increase of the void fraction of CICCs, typically from 30% to 40% for a CICC with ITER scale dimensions. A pre-OP heat treatment before OP is proposed in this study. The reduction of the wire diameter can be completed before the formation of the continuous superconducting phase, which would dramatically decrease the CICC void fraction. One Bi-2212 cable consisting of 84 wires, was first pre-OP heat treated successfully and after completing the OP heat treatment, the cable's transport performance was tested. The results showed good performance with a critical current ( I c ) of 35.7 kA at 5.8 T background field in 4.2 K, which is consistent with the predication.